2017
DOI: 10.1186/s12943-017-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-mediated upregulation of lncRNA HOXD-AS1 as a ceRNA facilitates liver cancer metastasis by regulating SOX4

Abstract: BackgroundSeveral of the thousands of human long noncoding RNAs (lncRNAs) have been functionally characterized, yet their potential involvement in hepatocellular carcinoma (HCC) remains poorly understood.MethodsLncRNA-HOXD-AS1 was identified by microarray and validated by real-time PCR. The clinicopathological significance of HOXD-AS1 was analyzed by Kaplan-Meier method. Chromatin immunoprecipitation was conducted to examine the mechanism of HOXD-AS1 upregulation. The role of HOXD-AS1 in HCC cells was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
363
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(376 citation statements)
references
References 52 publications
6
363
0
Order By: Relevance
“…In experiments investigating the underlying mechanism, PRMT1 accelerated HCC through the STAT3 pathway at the mRNA and protein levels. We also found that upregulating PRMT1 can increase STAT3 phosphorylation and thereby activate the STAT3 pathway, which can potentiate the development of HCC [22][23][24][25][26][27]. Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression.…”
Section: Discussionmentioning
confidence: 60%
“…In experiments investigating the underlying mechanism, PRMT1 accelerated HCC through the STAT3 pathway at the mRNA and protein levels. We also found that upregulating PRMT1 can increase STAT3 phosphorylation and thereby activate the STAT3 pathway, which can potentiate the development of HCC [22][23][24][25][26][27]. Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression.…”
Section: Discussionmentioning
confidence: 60%
“…Increasing literatures have confirmed that ceRNAs play key roles in many biological processes and immune responses [34,35], and miRNAs have been documented to be involved in the regulation of macrophage polarization [36,37] , similar to lncRNAs [14][15][16]. We were interested in identifying whether an mRNA-related ceRNA network existed during F. gigantica ESP-induced M2 cell polarization into M1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HOTAIR is associated with breast and liver cancer (30). HOTAIR is markedly reduced in lung cancer tissues, reinforcing the concept that the HOTAIR gene may have an important function in lung cancer (31). HOXD10 is another gene that is associated with cancer (30).…”
Section: Discussionmentioning
confidence: 83%
“…Although there is no clear difference in HOXD10 expression in cancerous tissues and healthy tissues, the gene has been revealed to be associated with lymphatic metastasis (32). Additionally, HOXD10 expression has been significantly increased in cancer tissues with lymphatic metastases (31). An in vitro experiment indicated that HOXD10 is modulated by the HOTAIR gene (10).…”
Section: Discussionmentioning
confidence: 99%